Evaluating Wall Street Journal survey forecasters: a multivariate approach - Robert Eisenbeis; Daniel Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2002)
This paper proposes a methodology for assessing the joint performance of multivariate forecasts of economic variables. The methodology is illustrated by comparing the rankings of forecasters by the Wall Street Journal with the authors' alternative rankings. The results show that the methodology can provide useful insights as to the certainty of forecasts as well as the extent to which various forecasts are similar or different.
Keywords: 330; Forecasting